Development and evaluation of different vaccines against duck pasteurellosis - Jesto George (Department of Dairy Science, College of Veterinary and Animal Sciences, 2010)
This study was undertaken to develop biofilm vaccines against duck pasteurellosis using oil, saponin and aluminium hydroxide as adjuvants and to experimentally evaluate their immunogenicity in ducks. Identity of P. multocida serotype A: 1 (DP1) used for study was confirmed by biochemical tests and by PM-PCR and pathogenicity was established in Swiss albino mice before vaccine production. The LD50 (11 w) of the DP1 isolate determined was 10 CFU / bird and MDT was 23.75 h in 11 week old ducklings when a high dose of 3 X 10 6 CFU of P. multocida per bird was given. At 11 Weeks age MDT gradually increased as the dose of inoculum decreased. In 21 week old ducks, the LD50 (21w) of the isolate DP1 was estimated to be 3 ×108 CFU of P. multocida and it showed that the Kuttanad duck had decreased susceptibility to pasteurellosis with age. On light microscopic studies planktonic cells appeared to be Gram negative coccobacillary, while biofilm cells were Gram negative and pleomorphic. Electron microscopic studies revealed that P. multocida could form well differentiated classic biofilm and 0.32 per cent TSB media supplemented 0.5 per cent chitin seemed to be excellent medium for biofilm formation by P. multocida. Four different vaccines viz. OV, OBV, SV and SAV were prepared and all of them were found to be sterile and safe. The oil adjuvanted vaccines (OV and OBV) offered better protection compared to saponin and aluminium hydroxide adjuvanted vaccine groups (SV and SAV) following primary vaccination, up to seven weeks. The modified oil adjuvanted vaccine prepared was not only found to be homogenous, but also more efficient in stimulating a humoral immune response and hence may be recommended.